The Phonological Interference in EFL Reading - Made Wahyu Mahendra; I Made Yogi Marantika (ELLITE, 2020)
The study aimed at exploring the phonological interference made by Pendalungan students in EFL reading, particularly in vowel phonemes. Pendalungan is an assimilation of two majority ethnics in Eastern Java; Java and Madura. Due to the unique characteristics of the language used by this group of community, it is assumed that the errors made by EFL Pendhalungan students might show different patterns as those found in either Javanese and Madurese students. To answer the problem of the research, the descriptive qualitative design was employed. There were eight students who belonged to the Pendalungan community, from a private university in East Java were taken as respondents. The secondary instruments used was an oral test of reading an English text. The finding showed that there were 12 incorrecty pronounced vowels; /ɪ, aʊ, ɔ:, e, Ʌ, əʊ, aɪ, ɪə, ə, ɒ, eɪ, æ/. The finding was analyzed based on the types of phonological interference, namely sound addition, sound omission, and sound replacement. The first two types have the least cases of two for each, while the last type has the most. Furthermore,the phonological interference emerged in the finding is somehow related to the nature of both languages, Javanese and Madurese. Inaccuracy mostly occurs because students pronounce the words as they are written.